2014
DOI: 10.1016/j.copbio.2013.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in microfluidic large scale integration

Abstract: In 2002, Thorsen et al. integrated thousands of micromechanical valves on a single microfluidic chip and demonstrated that the control of the fluidic networks can be simplified through multiplexors [1]. This enabled realization of highly parallel and automated fluidic processes with substantial sample economy advantage. Moreover, the fabrication of these devices by multilayer soft lithography was easy and reliable hence contributed to the power of the technology; microfluidic large scale integration (mLSI). Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 58 publications
0
68
0
Order By: Relevance
“…The external pneumatic air pressure that is applied to the membrane is controlled using a solenoid valve. Other valve technologies have been proposed, see [28] for a survey.…”
Section: A Technology and Fabricationmentioning
confidence: 99%
See 3 more Smart Citations
“…The external pneumatic air pressure that is applied to the membrane is controlled using a solenoid valve. Other valve technologies have been proposed, see [28] for a survey.…”
Section: A Technology and Fabricationmentioning
confidence: 99%
“…We will refer to these results when describing the design tasks. An overview of the recent developments in mVLSI is presented in [28]. Given the system specifications (e.g., application requirements, chip area), the mVLSI design flow starts with the schematic design (netlist) of the required biochip.…”
Section: Fault-tolerant Designmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite significant research activities in this highly multidisciplinary field over more than two decades, only few concepts have ultimately reached the level of commercialization. Studies addressing this issue [3,4] identified the lack of standardization and integration as the main barriers to acceptance by the end-user and thus to commercial breakthrough: After acquiring one of the few commercially available microfluidic products, the operator may face difficulties in connecting the microfluidic device to ancillary hardware, such as external supplies, valves, pumps and other microfluidic components [5]. In contrast to assessments in the early stages [6], which predicted silicon-based microsystem technology as the most promising approach for microfluidic applications, soft-matter-based and hybrid solutions have become more significant [7].…”
Section: Introductionmentioning
confidence: 99%